Accounting for Training Effectiveness: The Case of MIDA Training in Enterprise and Commercial Agriculture on Behaviour and Practices of Rice Farmer-Based Organisations - C. K, Osei; J. A, Bakang; F, Nimoh (Asian Journal of Agriculture and Rural Development, 2013)
This study was designed to determine the effectiveness of a Farmer and Enterprise Training in Commercial Agriculture (FETCA) programme on behaviour and practices of rice farmers in the Sekyere East District of Ashanti Region of Ghana. For this purpose, the study adopted the Kirkpatrick framework as a guide in assessing training effectiveness and used the before- and after-tests to assess change in behaviour. Both quantitative and qualitative data were collected and analysed through descriptive analytical statistics and the z-test. The results of the study revealed that the MIDA-Farmer and Enterprise Training in Commercial Agriculture (FETCA) programme significantly upgraded the technical know-how of members of Farmer-Based Organisations (FBOs) to adopt key recommended production practices and improved their organisational capacity building behaviours. There is evidence of shared knowledge and experiences in production-based rice activities, building capacity and developing financial skills with colleague farmers, farm family and farm workers, indicating a multiplier effect of the FETCA programme. The results reinforces the view that focus on Organisational Capacity Building modules, Technical Capacity and Business Development modules, are important in FBO training programmes in Ghana.